Accurate quantification of chromosomal lesions via short tandem repeat analysis using minimal amounts of DNA - Jann, Johann-Christoph; Nowak, Daniel; Nolte, Florian; Fey, Stephanie; Nowak, Verena; Obländer, Julia; Pressler, Jovita; Palme, Iris; Xanthopoulos, Christina; Fabarius, Alice; Schlenk, Richard Friedrich; Hofmann, Wolf-Karsten; et al. (Journal of medical genetics, 2017)
Background: Cytogenetic aberrations such as deletion of chromosome 5q (del(5q)) represent key elements in routine clinical diagnostics of haematological malignancies. Currently established methods such as metaphase cytogenetics, FISH or array-based approaches have limitations due to their dependency on viable cells, high costs or semi-quantitative nature. Importantly, they cannot be used on low abundance DNA. We therefore aimed to establish a robust and quantitative technique that overcomes these shortcomings. Methods: For precise determination of del(5q) cell fractions, we developed an inexpensive multiplex-PCR assay requiring only nanograms of DNA that simultaneously measures allelic imbalances of 12 independent short tandem repeat markers. Results: Application of this method to n=1142 samples from n=260 individuals revealed strong intermarker concordance (R²=0.77-0.97) and reproducibility (mean SD: 1.7%). Notably, the assay showed accurate quantification via standard curve assessment (R²>0.99) and high concordance with paired FISH measurements (R²=0.92) even with subnanogram amounts of DNA. Moreover, cytogenetic response was reliably confirmed in del(5q) patients with myelodysplastic syndromes treated with lenalidomide. While the assay demonstrated good diagnostic accuracy in receiver operating characteristic analysis (area under the curve: 0.97), we further observed robust correlation between bone marrow and peripheral blood samples (R²=0.79), suggesting its potential suitability for less-invasive clonal monitoring. Conclusions: In conclusion, we present an adaptable tool for quantification of chromosomal aberrations, particularly in problematic samples, which should be easily applicable to further tumour entities.
Published online first 9 June 2017
Gesehen am 30.07.2018